Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. The impact of information technology on human resource management practices from the perspective of education administration employees in Jeddah Ms. Arwa Mohamad Alharbi, Ms. Henda Salem Matoussi 2. The Impact of Accounting Information Systems’ Characteristics on Organizational Performance by Using Leadership Style: A Field Study on Saudi Industrial Corporate Mrs. Shahad Ahmed Alaseeri, Co-Prof. Rawia Reda Obaid 3. Water problem and its implications for sustainable development Wael Mohammed Al-Malki, Saleh Ibrahim Al-Shamsan, Abdulmalek Faisal Al-Alewi, Mansour Abdullah Al-Shebil, Issam Suleiman Al-Naser 4. An econometric study of the Phillips curve with inflationary expectations in the Saudi economy for the period 1997-2022 Dr. Emad Adnan Matyori 5. The Assumption of the Judiciary in Palestinian Territories: Balancing Islamic Law and Secular Law Mr. Gaber Mohammed Alorgan 6. The Impact of Strategic Planning on Key Performance Indicators in the Saudi Private Sector in Light of Saudi Vision 2030 Dr. Arwa Mohammed Alawwad 7. Forensic accounting and its role in reducing financial corruption A field study applied on some judicial institutions in the Kingdom of Saudi Arabia Dr. Mohammed Elsadig Abdallah